1960
DOI: 10.1111/j.1365-2133.1960.tb13888.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperaemia of the Deeper Cutaneous Vessels After Irradiation of Human Skin With Large Doses of Ultra-Violet and Visible Light.

Abstract: IMMEDIATE pigmentation " is described as a brownish-red or greyish discoloration of human skin proA^oked by heavy doses of long-wave ultraviolet and visible light (320-450 nyi, Hamperl et aL, 1939 ; Wiskemann and Wisser, 1956 ; Wisser, 1955). It deA^elops during the irradiation, in contrast Avitli the normal sunburn pigmentation, which accompanies the erythema some days after an irradiation Avitli small doses of sliort-waA^e ultra-violet light (297 nyi). Tliis immediate pigmentation partly fades within one or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1963
1963
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Mediators released under the effect of visible light and action spectrum of erythema in the visible range are not yet fully studied. A 1960 study (11) described the erythema caused by UV radiation and visible light. It found that the UV erythema caused by 250 and 297 nm is the result of capillary dilatation, and such wavelengths penetrate only very superficially into the upper dermis.…”
Section: Biologic Effects Of Lightmentioning
confidence: 99%
“…Mediators released under the effect of visible light and action spectrum of erythema in the visible range are not yet fully studied. A 1960 study (11) described the erythema caused by UV radiation and visible light. It found that the UV erythema caused by 250 and 297 nm is the result of capillary dilatation, and such wavelengths penetrate only very superficially into the upper dermis.…”
Section: Biologic Effects Of Lightmentioning
confidence: 99%
“…A 1960 study found UV (250 and 297 nm) erythema was caused by capillary dilatation, these wavelengths only penetrating superficially into the upper dermis. Longer wavelengths penetrate deeper into the dermis resulting in dilatation of vessels of the subpapillary plexus [11].…”
Section: Visible Lightmentioning
confidence: 99%
“…A 1 £ 2-cm area of the upper arm of a test subject (number of subjects not stated) was moistened with the extract, and the site was covered after the solvent evaporated. After 1.5 hours, the test area was irradiated for 5 minutes using an apparatus (described by Rottier and Van der Leun 1960) that had as its light source "a water-cooled super high-pressure mercury lamp (SP 500, Philips)." Monochromatic light (366 m¹), obtained using an interference lter, was used.…”
Section: Phototoxicitymentioning
confidence: 99%